Socialist Market Economy In Viet Nam - Impact And Policy Response - Duc Huu , Nguyen (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Each country or territory can have different levels of development, but they are operated by the direct or indirect dominance of the political institutions. Until now there has been a widespread recognition of the role of political institutions for economic development growth. Despite this, there is no general agreement on the therion of institutions and the connection between institutions and development. Since 1986, with its innovation policies and the implementation of extensive economic reforms, Viet Nam has made achievements in socio-economic development, and has escaped from the list of poor countries to become low-middle-income countries. This impressive step has brought many new opportunities but also comes with new challenges that need to be overcome so that Vietnam can become an industrial country and not fall into the "Middle Income". This article overviews the market economic model and explains the choice of market economy model in Vietnam in the socialist institutions. The article uses a second document and demonstrates that Vietnam's policy response is wise in the process of integration and globalization in the development trend.